Development of Law on Protection from Disability-Based Discrimination in Russia - Shinkareva, Elena (Białostockie Studia Prawnicze, 2018)
The article describes and analyses current law on protection from disability-based discrimination in Russia. Amendments in the national legislation were adopted in accordance with the Convention on the rights of persons with disabilities ratified in 2012. Prohibition of discrimination on the grounds of disability is included into the law. However, the development of the mechanisms of protection of the right not to be discriminated against has only just started. While a special anti-discrimination law is not yet devised, legal actors have to apply the existing legal provisions which do not cover all aspects of protection from disability-based discrimination. len.shinkar@mail.ru Elena Shinkareva – Legal adviser in the Regional branch of the Deaf Organization in Arkhangelsk, lecturer at the Institute of Open Education, candidate of sciences in law (Moscow State Social University, 2007), Ph.D. research fellow (UIT The Arctic University of Norway, 2013– 2016). Institute of Open Education in Arkhangelsk Decision of the Cheryomushky district court of Moscow, 17 October 2008, case no. 2-5572/08. The case description and documents are available on the web-site of the Non-Governmental Organization “Perspektiva” (Moscow) https://perspektiva-inva.ru/protec-rights/trial/851-vw-851 (08.08.2018). Decision of the Supreme Court of 14 November 2012, case no. АКПИ12-1299, http://www.consultant.ru/document/cons_doc_LAW 139341/. Federal Act On social protection of invalids in the RF, dated November 24, 1995, No. 181-FZ. UN Committee on the Rights of Persons with Disabilities. Guidelines on periodic reporting to the Committee on the Rights of Persons with Disabilities, including under the simplified reporting procedures, CRPD/C/3. UN Convention on the Rights of Persons with Disabilities. 23 4 57 66